THE UTILITY OF EDUCATIONAL VIDEO IN IMPROVING AWARENESS OF BONE HEALTH IN PRE-SCHOOLS AND PRIMARY SCHOOL-AGED CHILDREN AND EDUCATORS IN SINGAPORE - Gani, Linsey; Chan, Elizabeth; Pang, Janelle; Low, Christina; Bin, Ang Seng; Bee, Chionh Siok (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION The foundation of skeletal health begins as early as in utero with the majority of bone mass gained in childhood and adolescence. It is estimated that a 10% increase in peak bone mass would delay the onset of osteoporosis by 13 years in women. Thus, optimizing factors that would help in achieving peak bone mass would assist in the primary prevention of osteoporosis. In this study, we piloted an educational video in the preschool and primary school population to assess its effectiveness in increasing awareness of bone health and activity. METHODOLOGY A team of doctors, dieticians, and physiotherapists worked together to create an educational video to increase awareness of bone health. Major themes incorporated included: 1. The importance of strong bones and growth of bones in children; 2. The role of adequate calcium in a healthy diet; and 3. The importance of exercise in bone health. The educational video was piloted in Singapore from June to September 2022. The video was created in an animated format to allow greater appeal to younger children. The teacher’s activities deck along with suggestions for learning points was also shared with the various schools and preschool institutions. The work was conducted with the collaboration of the Health Promotion Board (HPB), Singapore. Feedback on the educational video was also collected at the end of the pilot period. RESULTS For 3 months, publicity was conducted in 1,800 preschools and 170 primary schools. Feedback was received from 10 primary schools and 24 preschool centers. The educational video was also hosted on YouTube and received over 1,800 views. Over 5,000 students were reached based on the feedback given by the schools. The feedback found that 88% of the users found the resources were useful with age-appropriate content. There was a very high level of satisfaction with 91% stating a satisfaction level scale of 4-5. The majority of feedback was obtained from the kindergartens 1 and 2 and primary levels 1-4. About 77% found that the resources were easy to use. CONCLUSION An animated educational health video with an appealing design and simple contents is an easily administered tool and effective in increasing awareness of bone health. Hosting the video on YouTube also allowed greater outreach to those beyond the schools. Further follow-up is needed to ascertain the effectiveness of this educational tool in changing overall health behaviours and its long-term impact on bone health in Singapore.